ECONOMIC ACTIVITY IN AGRICULTURE IN THE PERSPECTIVE OF EMBEDDEDNESS THEORY: THE CASE OF POLAND - Dudek, Michał (Economics of Agriculture, 2016)
The paper presents the concept of embeddedness of economic activity in relation to agriculture. In this perspective, economic activity can be considered dependent on cognitive structures, structures of social relations, culture, and political institutions. It has been concluded that the idea of embeddedness can be an interesting and useful analytical tool for the analysis of economic activity undertaken by farmers. The article presents an analysis of the state of the art, as well uses selected information and data on the methodology of panel surveys carried out by the Institute of Agricultural and Food Economics – National Research Institute. Based on the analysis of the embeddedness theory, it is argued that embeddedness is not a coherent theoretical concept but rather a potential framework for investigating various economic issues. One of these issues is agricultural activity. Embeddedness framework constitutes a scheme which could organize an alternative approach to economic actions to mainstream agriculture economics.